GARIS DI LAPANGAN HIMPUNAN BILANGAN BULAT MODULO 17 - Denni Hariati Sinaga; Idha Sihwaningrum; Ari Wardayani (Universitas Jenderal Soedirman, 2013)
n this paper we discuss rational trigonometry in the field F17 ,in particular point, lines and their properties. A unique property in this field is given by the null lines.